First Nations student engagement in secondary school: enhancing student success in a northern Eeyou community - Pashagumskum, Sarah Jane (2014)
This study investigated engagement and disengagement factors for high school students in a northern Eeyou community using a mixed methods participatory approach. A quantitative survey, administered to a stratified sample of 60 students (representing 17% of the total population of 351), measured the presence of engagement factors previously identified in First Nations student engagement, drop-out, and school-leaving literature. Only descriptive statistics were used, as this part of the study was exploratory, determining the presence of these factors among the student population. Quantitative results showed a lack of cultural relevancy in the curriculum of the school, poor relationships between peers and between students and adults in the school, and a lack of perceived student empowerment. Qualitative methods were based in constructivist grounded theory and included interviews and focus groups with five students, seven school staff members, and eight members of the wider community. Qualitative data served to elaborate upon quantitative results and identified similarities and differences between Eeyou student engagement factors and mainstream student engagement factors. Qualitative results showed a lack of respectful and caring relationships in the school, areas for improvement in teaching approaches, problems with teachers’ understanding and sensitivity towards Cree culture and language, curriculum issues related to culture, a lack of community involvement, and a need to improve the school’s receptiveness to student needs and perspectives. The dissertation concludes with recommendations for enhancing student engagement by enhancing students’ abilities to attend school and remain in school within the school studied. These recommendations may also be relevant for enhancing First Nations on-reserve student engagement in general. Recommendations point to a need to increase the cultural content of the curriculum in authentic ways, increase students’ sense of belonging in the school, provide a rigorous education program, and support the creation of positive relationships between peers and between students and teachers in the school. These changes can be made through changes to classroom and school practices. It is also recommended that an instrument to assess onreserve high school student engagement be created, and that further research include both studies of the effects of in-school counseling and teacher absence on First Nations student engagement.